2006
DOI: 10.1063/1.2354451
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing method for n-type porous silicon based on Hall effect without illumination

Abstract: Articles you may be interested inVertical hybrid microcavity based on a polymer layer sandwiched between porous silicon photonic crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Figure 5 shows the PL spectra of PS samples in all cases. In the non-annealing case (case A), an orange-red emission at the 610 nm peak is observed, which is the common result in the previous reported papers [3,16,17]. On the other hand, however, an obvious blue-shifting occurs in all postannealing cases (case B-F) in this study.…”
supporting
confidence: 88%
“…Figure 5 shows the PL spectra of PS samples in all cases. In the non-annealing case (case A), an orange-red emission at the 610 nm peak is observed, which is the common result in the previous reported papers [3,16,17]. On the other hand, however, an obvious blue-shifting occurs in all postannealing cases (case B-F) in this study.…”
supporting
confidence: 88%
“…3b). Similar variations in PL intensity across samples was also found by Lin et al, [22] who used the Hall effect to drive holes to the silicon/ electrolyte interface. In the present work, the application of a lateral potential field and the resulting current flow across the sample is believed to draw electrons away from the silicon substrate's surfaces, as shown in Figure 1a, thereby increasing the hole concentration at the silicon/electrolyte interface allowing etching to proceed at a greatly accelerated rate.…”
Section: à2supporting
confidence: 70%
“…[21] The second technique was to use the Hall effect, that is, application of perpendicular electric and magnetic fields, to drive holes to the silicon/HF interface. [22] However, these techniques suffer disadvantages in the form of difficulties in either their sample preparation technique, lack of ease in experimental arrangement, or control over the PSi formation rate.…”
mentioning
confidence: 99%
“…It can be found that along the longitudinal direction of the n-type PSi the morphology is varied from highly interconnected pores to quasitriangle and triangle pores ( Fig. 2(a)-(c)), and the diameter of the pores is gradually decreased too, similar to the result given by Lin [30]. It is believed that the applied lateral potential would result in a potential gradient along Si wafer, which is schematically drawn in Fig.…”
Section: Resultssupporting
confidence: 73%